2019
DOI: 10.36487/acg_rep/1915_58_mundodi
|View full text |Cite
|
Sign up to set email alerts
|

Growth of rye grass and clover in artificial topsoils: a case study

Abstract: The Latrobe Valley region of eastern Victoria houses three major mines which burns lignite for power generation and is referred to as the power house of Victoria. These mines are looking for sustainable ways to manage their waste and achieve successful mine rehabilitation. One of the problems to be addressed for attaining successful mine rehabilitation is the scarcity of topsoils for vegetation cover. The possible solution for overcoming this problem is the use of artificial topsoils (ATS) developed using wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The addition of anaerobically digested paper mill waste, called effluent sewage recovery (ESR), and waste lignite from the mine (BC) has increased the organic matter and nutrient content of the soils. A lysimeter field study deemed these soils safe for mine rehabilitation, and further greenhouse study (Mundodi 2020;Mundodi et al 2019) showed that they provide a substrate suitable for plant growth, although relatively high salinity has delayed germination of clover. Table 1 summarises all the substrates used in the present study and their basic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of anaerobically digested paper mill waste, called effluent sewage recovery (ESR), and waste lignite from the mine (BC) has increased the organic matter and nutrient content of the soils. A lysimeter field study deemed these soils safe for mine rehabilitation, and further greenhouse study (Mundodi 2020;Mundodi et al 2019) showed that they provide a substrate suitable for plant growth, although relatively high salinity has delayed germination of clover. Table 1 summarises all the substrates used in the present study and their basic properties.…”
Section: Introductionmentioning
confidence: 99%